Factors affecting fish production levels in aewora village, maurole district ende district - Yuliana Sedho (Sean Institute, 2024)
This research aims to determine and explain the factors that influence the level of fish production in Aewora Village, Maurole District, Ende Regency. The population in this study were all members of the fishing community who make their living as fishermen in Aewora Village, totaling 129 people. The sample in this study amounted to 100 people using simple random sampling techniques. The data collection technique in this research used a questionnaire. The data analysis technique uses Multiple Linear Regression analysis with calculations using the SPSS 21 program. Based on the results of the analysis that has been carried out, this research shows that education has a negative and insignificant effect on fish production, while fishing gear skills have a positive and significant effect on fish production. The results of this research can be used to develop effective policies and strategies for activities to increase fish production and income of fishing communities in Aewora Village, Maurole District, Ende Regency, and it is hoped that the local government can provide assistance with fishing equipment and education to improve the skills of fishermen through training programs.